Understanding media coverage on terrorism and its relations with islamophobia / Putri Nur Adriana Alya Ahmad ...[et al.] - Ahmad, Putri Nur Adriana Alya; Redzuan, Naja Amira; Gubak, Jefferson; Abd Latiff, Zulkifli (Centre For Media And Information Warfare Studies, 2021)
Terrorism has been a daily issue, or if not, one of the main issues reported in the media be it in the local or foreign media. News coverage on terrorism has escalated since the tragedy of 9/11. There have been many cases where the media particularly, the Western media coverage on terror acts are biased towards Muslims and Islam which created a long-lasting images and stereotypes of this group. Exposure to violent media stereotypes of Muslims has been shown to boost Westerners' encouragement for antiMuslim policies such as military action abroad and civil limitations at home. Muslims are usually depicted as violent, aggressive, and drawn to terrorism in a variety of media covering newspapers, cable news, television, movies and video games. The media is a predominant component of popular culture, with the potential to set the agenda. As a result, when an agenda is aligned across media outlets, the media has the ability to create association for people, race, culture and religion. This study aimed to explore the roles of media reporting of terrorism in propagating Islamophobia that shapes our news reporting and the adoption of the war journalism theory. In doing so, a qualitative approach with thematic analysis was undertaken by employing conceptual research to study the findings of previous research on the related subject of media, terrorism, and the phenomena of Islamophobia. The finding showed that the media succeeded in instilling fear into the public towards Islam and Muslims through the news reporting on terrorism phenomena.